ADC values as a biomarker of fetal brain maturation - Kobal, Lucija (Radiology and oncology (Ljubljana), 2023)
Background. During the period of fetal development, myelination plays a key role and follows specific time and spa-tial sequences. The water content in the brain is inversely proportional to myelination – the more myelinated the brain, the lower the water content in it. The diffusion of water molecules can be quantitatively assessed using the apparent diffusion coefficient (ADC). We were interested in whether, by determining the ADC values, we could quantitatively evaluate the development of the fetal brain. Patients and methods. The study included 42 fetuses with gestational age 25 to 35 weeks. We manually selected 13 regions on diffusion-weighted images. Statistically significant differences between ADC values were checked using one-way analysis of variance and Tukey’s post hoc test. The relationship between the ADC values and the gestational age of the fetuses was then assessed using linear regression. Results. The average gestational age of the fetuses was 29.8 ± 2.4 weeks. ADC values in the thalami, pons and cerebellum differed significantly among each other and from the ADC values in other brain regions. In the thalami, pons and cerebellum, linear regression showed a significant decrease in ADC values with increasing gestational age. Conclusions. ADC values change with the increasing gestational age of the fetus and differ among different brain regions. In the pons, cerebellum and thalami, the ADC coefficient could be used as a biomarker of fetal brain matura-tion since ADC values decrease linearly with increasing gestational age.
Keywords: ADC; biološki označevalec; biomarker; diffusion; diffusion-weighted imaging; difuzija; difuzijsko uteženo MRI; fetal brain maturation; mielinizacija; myelination; zorenje možganov ploda